Unlocking Imagination: The Impact of English Stories in the Classroom - Umar, Umar (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
This article explores the impact of English stories in the classroom, focusing on how storytelling unlocks students’ imagination and enhances their language development. Through a mixed-methods approach, including literature review, case studies, classroom observations, and student interviews, the study investigates the role of stories in stimulating creativity, improving language skills, and fostering critical thinking. The findings highlight how stories introduce new vocabulary in context, promote listening and speaking skills, and strengthen reading comprehension and writing abilities. Additionally, storytelling serves as a powerful tool for increasing student engagement and motivation while also developing empathy and cultural awareness. The article emphasizes the educational benefits of using narratives to not only teach language but also to encourage a deeper connection with the material and a broader understanding of diverse perspectives. The conclusion advocates for the continued integration of storytelling in English language curricula, emphasizing its potential to unlock students’ imaginations and support their holistic development as language learners and global citizens.